2017 AIChE Spring Meeting & 13th Global Congress on Process Safety : 19th Process Plant Safety Symposium (PPSS) (Center for Chemical Process Safety/AIChE, 2017)
Each year the Center for Chemical Process Safety (CCPS) and the AIChE Safety & Health Division present the world's largest gathering of process safety professionals, the Global Congress on Process Safety (GCPS). The focus of the Plant Process Safety Symposium (PPSS) focus is to provide proven best practices, perspectives, methods and tools that can be readily practiced and provide value to personnel at the plant level. PPSS is inviting the process safety practitioners to submit abstracts for the upcoming 13th Global Conference on Process Safety in 2017. The conference will be held in San Antonio, TX March 26-30, 2017. The abstract should offer a brief (less than 200 words) account of the contents, conclusions, and the relevance to the topic area.
Keywords: Chemical process control.; Chemical plants -- Safety measures.; elektronické knihy; electronic books